The Effect of the Recruitment System on Interest in Applying to Work Abroad Mediated by Compensation in the Labor Force in Bekasi Regency - Hidayat, Denny (Lentera Ilmu Nusantara, 2025)
This research was conducted with the aim of determining the influence of the recruitment and compensation system on the interest of applying to work abroad by the workforce in Bekasi Regency. This research was conducted on the workforce in Bekasi Regency with a sample of 95 respondents. The method in this study uses a quantitative method with random sampling. Data collection in this study uses an online questionnaire through google forms. The data analysis used in this study uses SmartPLS software version 3.0. Based on the results of data processing research, the recruitment system affects interest in working, the recruitment system affects compensation, compensation affects interest in applying for work and the recruitment system through compensation affects interest in applying for work.